Comparative Analysis of Quality of Service (QoS) Parameters in Various Local Area Network Architectures : A Literature Review - Mohammad Hafis Trialdian; Rehan Wahyu Andika; Ali Masngudin (PT Mekar Research and Publishing, 2026)
Quality of Service (QoS) is a key indicator in evaluating the effectiveness of a computer network infrastructure. This article presents a systematic literature review regarding the technical performance comparison of Star, Bus, and Ring topologies, focusing on throughput, latency, and packet loss parameters. The analysis was conducted on 30 scientific sources covering both conventional and modern network simulations, such as Software Defined Network (SDN). The results of data synthesis show that Star topology dominates in transmission stability at low to medium loads with an average throughput value of 94.5 Mbps. However, Ring topology shows superior performance in programmed network environments (SDN) and high redundancy scenarios. Bus topology, although economical, experiences significant QoS degradation as data traffic load increases. This study provides technical guidance for network designers in optimizing architecture based on specific performance demands.